Youtube Analytics Channel Visualization Results Using Google Data Studio and Klipfolio - Tangang Qisthina Handayani Zatadini; Achmad Farid Wadjdi; I Made Wiryana; Cahya Maharani Badzlina Zataamani (Journal on Education, 2024)
Demonstrate the power of Big Data Analytics using Google Analytics as a platform work flow. First open the YouTube channel, then start recording of the channel analytics is done here automatically by Google. This data is exported from YouTube Analytics to Google sheets and then is fed to Google Analytics. After analyzes the data, it is now integrated with Google Data Studio and Klipfolio. Google Data Studio makes use of AI (Artificial Intelligence) insights techniques that can generate artificial intelligence and prediction-based report graphs which can be analyzed by the end user. In the future, not only YouTube, but any Google products or Google service data can be fed to Google Analytics and integrated in Google Data Studio for artificial intelligence based on Big Data Analytics.